Therapy adherence and polypharmacy in non‐institutionalized elderly from Amares county, Portugal - Pinto, Isabel C. (2018)
Polypharmacy is frequent in elderly, and therapy adherence is a crucial component to achieve the effectiveness of treatment, but the complex therapies in elderly can lead to therapy non-adherence, increasing costs and several health risks. Objectives: To estimate the prevalence of therapy adherence, polypharmacy and associated factors in elderly. Methods: This cross-sectional study was based on a questionnaire, with MAT scale (measure of adherence to therapy) validated for the Portuguese population (Delgado & Lima, 2001), applied to 159 elderly (≥65 years) living in his home in Amares county, in northern Portugal. To assess therapy adherence, those whose average adherence levels were ≥5 were called adherent, and it was considered as polymedicated seniors taking ≥5 drugs. It was used descriptive statistics, correlations were accessed using qui-square test and adjusted residuals (AdR) for variables categories, with a significance level of 5%. Results: The sample consisted mainly of females (54.7% vs. 45.3%), aged between 65 and 96 years old (mean 74.6), while 50.3% was between 65-74 years old. The participants show good therapy adherence (69.8%), being highly polymedicated (58.5%) with an average of 5.5 different drugs administered per day. Non-adherence is associated with having mental disorders (p=0.002) and respiratory system diseases (AdR=2.0), and seems to be related with being polymedicated (AdR=1.7) and bad health perception (AdR=1.3). Having hypertension, cholesterol, depression, mental disorders (p=0.001), pain (p=0.003) and diabetes (p=0,014) are related to polypharmacy. Conclusions: This study shows a considerable prevalence of therapy adherence and polypharmacy, being several factors associated with these phenomena.